A new species of Pristimantis (Anura: Strabomantidae) from the Brazilian Cerrado - Maciel, Natan Medeiros; Vaz-Silva, Wilian; de Oliveira, Renan Manoel; Padial, José Manuel (Zootaxa, 2012)
A new species of Pristimantis (Anura: Strabomantidae) from the Pristimantis conspicillatus group is described from theCerrado biome in central Brazil. Pristimantis ventrigranulosus sp. nov. is found in riparian forests associated with a par-ticular palm tree called “babaçú” (Attalea speciosa: Aracaceae) in northwestern Goiás state of Brazil. The new species isonly known from the type locality: Fazenda Macaúba (16°35’23” S; 51°47’43” W, approximately 400 m above sea level),Piranhas Municipality in the state of Goiás. The new species differs from the other species in the P. conspicillatus groupmainly by having, an homogeneously granular belly, Finger I > Finger II, dorsal skin coarsely shagreen, toe and fingerfringes weakly developed or absent, presence of basal webbing and tarsal fold, single nuptial pad on thumb, moderatelydeveloped and round discs on Fingers III and IV, and higher dominant frequency than other Pristimantis with similar calls(ranging 3451.8−4334.8 Hz). The new species shows an advertisement call equal in structure to the calls of P. dundeei, P. fenestratus, P. koehleri and P. vilarsi. Pristimantis dundeei is transferred to the P. conspicillatus group.